2010
DOI: 10.1590/s0100-29452010005000090
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de Passifloraceas, fungicidas e Trichoderma para o manejo da Podridão-do-colo do maracujazeiro, causada por Nectria haematococca

Abstract: RESUMO -A baixa produtividade do maracujazeiro-amarelo é devida, muitas vezes, a problemas fitossanitários, sendo a Podridão-do-colo, causada por Nectria haematococca, um dos principais problemas na maioria dos Estados produtores do Brasil. O controle desta doença é basicamente preventivo, evitando a introdução do agente patogênico na área. Sendo assim, o presente trabalho teve como objetivos: a) avaliar o comportamento do maracujazeiro-amarelo 'Afruvec', 'IAC 275' e 'Maguary', do tipo pé-franco, e 'Afruvec' e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
4
0
3
Order By: Relevance
“…Therefore, the same results were not found for the species P. cincinnata and P. alata, since in this study they showed high resistance and high susceptibility, respectively. Fischer et al (2010b) conducted studies in orchards where the disease had occurred and found that the species P. alata and P. suberosa used as rootstock were more resistant to stem rot compared to the non grafted plants. In this study, under controlled conditions, the same species exhibited little resistance to the disease.…”
Section: Group Group Group Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the same results were not found for the species P. cincinnata and P. alata, since in this study they showed high resistance and high susceptibility, respectively. Fischer et al (2010b) conducted studies in orchards where the disease had occurred and found that the species P. alata and P. suberosa used as rootstock were more resistant to stem rot compared to the non grafted plants. In this study, under controlled conditions, the same species exhibited little resistance to the disease.…”
Section: Group Group Group Groupmentioning
confidence: 99%
“…The chemical control of collar rot has been tested (FISCHER et al, 2010b;SILVA et al, 2014), but its efficiency is still incipient because of the residues that remain in the soil and the increased production costs. Moreover, the characterization and exploitation of genetic variability among species of Passiflora may provide valuable sources of resistance for the control of these diseases in the field (use as rootstock) or use in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En un ensayo sobre fertilización del cultivo de maracuyá con fuentes N-P-K en Ecuador, se encontró que el número de días transcurridos desde el trasplante hasta la cosecha con uso de dosis de 100-50-80 kg ha -1 en forma bimensual, se redujo en comparación al resto de los tratamientos evaluados; adicionalmente, dicho tratamiento duró 186 días, para iniciar la cosecha, mientras que en el testigo inició a los 210 días (Pereira, 2015). Los resultados encontrados en la presente investigación mostraron mayor precocidad para el inicio de la etapa productiva del cultivo bajo las condiciones de experimentación, Fischer et al (2010;2016) señalaron que esto podría deberse a que en regiones más cercanas al Ecuador, el inicio de la fructificación tiende a ser más precoz.…”
Section: Discussionunclassified
“…Con relación al rendimiento, Borges et al (2006) encontraron una disminución de la productividad con la aplicación de dosis más altas de nitrógeno (0, 100, 200, 400 y 800 kg N ha -1 año -1 ), posiblemente atribuidas a la función del crecimiento vegetativo, resultando en una alta producción de hojas y reduciendo el número de flores y, por consiguiente, menos cantidad de frutos. Las menores dosis de nitrógeno (T1 y T2) obtuvieron los menores rendimientos; esto tiene relación con que dicho nutrimento está fuertemente asociado al incremento en la productividad de los cultivos (Fischer et al, 2010).…”
Section: Discussionunclassified